Perkembangan Ekspor dan Impor Sumatera Utara pada Tatanan Hidup Baru - Sheyila Putri; Aldy Fernando Lubis; Annisa Fahira; Deva Kumala Sari; Dewi Chofifah (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The level of a province can be seen from its economic growth, seen from the aspect of the value of exports and imports which have an influence on a trade between provinces. After the occurrence of covid-19 which had a major impact on Indonesian trade and the global economy. As a result of the pandemic, there have been major changes in world trade patterns, such as the lockdown system implemented in Indonesia. This study aims to determine the development of exports and imports of North Sumatra Province through indicators of export and import values. The data analysis technique in this research is descriptive data analysis. The source of data in this study is secondary data taken in (2016/2020) which is downloaded via www.bps.go.id, especially export and import data during the development of a new economic life order in North Sumatra Province. The results show that there is an increase that can be seen from the increase in the volume and value of imports and exports in a province, a decrease in the volume and value of imports and exports of imports, the development of a new economic order of life. With good economic growth, it will increase national income, the community will be prosperous in terms of the economy. In the last decade, exports continued to increase in 2021 to reach Rp. 13 trillion. Many studies have stated that in the past year, export-import cases have fluctuated during the COVID-19 period. And this pandemic has taught us the need to encourage export and import diversification, diversification of supplying countries and product destinations. produced in order to develop in a new life order. Keywords: Export, Import, New Era, Economic Growth